Phonogram 108.077 (Brazilian Odeon): George W. Johnson’s lundum (Per Musi, 2011)
Through an examination of the phonogram Gargalhada (pega na chaleira) [laughter (picking up the kettle)], chansonnette sung by Eduardo das Neves, the origin of the expression “pegar na chaleira” (bootlicking) emerges, together with incongruities in the Instituto Moreira Salles online catalogue. Probably recorded in 1906, six years before the establishment of the Odeon plant in Rio, the piece was labelled as a lundum, a paradigmatically Afro-Brazilian genre, in the 1915–1926 catalogues. The music and laughter that Neves appropriates to himself were created by George W. Johnson, the first black star of early phonography, and reused in other Casa Edison (Brazilian Odeon) recordings on sale from 1913 to 1919. But while the former North American slave ridicules himself in accordance with white stereotypes, the self-designated crioulo stages a satire on the behaviour of upper-class Rio de Janeiro males. In this process, the coon song turns into its antithesis.